Discovery and Characterization of Protein‐Modifying Natural Products by MALDI Mass Spectrometry Reveal Potent SIRT1 and p300 Inhibitors1. Issue 19 (8th April 2013) - Holzhauser, Susanne; Freiwald, Anja; Weise, Christoph; Multhaup, Gerd; Han, Chung‐Ting; Sauer, Sascha
<x xml:space="preserve">Abstract</x> A straightforward MALDI MS method facilitates the unbiased screening and characterization of compounds that modify protein activity. This procedure can be used to circumvent analytical problems deriving from compounds with autofluorescence. Various posttranslationally active enzymes like deacetylases, acetyltransferases, kinases, phosphatases, and methyltransferases can be studied in the presented way.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>